Coprinopsis alnivora (Psathyrellaceae), a rare species from North America is discovered in Europe - Bednár, Radovan; Červenka, Ján; Arendt, Darina; Szabóová, Dana; Krisai-Greilhuber, Irmgard; Pošta, Ana; Mešić, Armin; Tkalčec, Zdenko (Phytotaxa, 2022)
A rare species, Coprinopsis alnivora, was previously known from the type collection in Washington State, USA. Afterward, 11 additional samples were collected from five new host trees at nine localities in Europe (Austria, Croatia, and Slovakia). The species indicated a preference for growth in cavities or wounds of living deciduous trees. Its mycelium and basidiomata were successfully cultivated under laboratory conditions. A detailed morphological description of the basidiomata supplemented with colour photographs and line drawings is provided. Delimitation characters from similar species are discussed. Molecular phylogenetic relationships within the genus Coprinopsis were inferred from ITS rDNA sequences and are presented by a phylogram. Molecular genetic analyses revealed that C. alnivora represents a genetically well-delimited species with six known haplotypes.